Pengaruh Bi-Rate, Inflasi, dan IHSG Terhadap Dana Pihak Ketiga Perbankan Syariah di Indonesia Tahun 2020-2024 - Mochammad Zaki; Rini Hidayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of macroeconomic variables, namely the BI-Rate, inflation, and IHSG, on Third Party Funds (TPF) at Islamic Commercial Banks and Islamic Business Units in Indonesia during the 2020–2024 period. The data used is monthly time series data spanning five years, with 60 observations. The analytical method used is multiple linear regression with the Ordinary Least Squares (OLS) approach, adjusted for Heteroskedasticity and Autocorrelation Consistency (HAC) to address violations of the classical assumptions. The results show that the BI-Rate and the IHSG have a positive and significant effect on TPF, while inflation has no significant effect. Simultaneously, all three independent variables have a significant effect on TPF with a coefficient of determination of 93.6%, indicating that the model is very effective in explaining variations in TPF. These findings demonstrate the importance of macroeconomic indicators in the accumulation of public funds in the Islamic banking sector.